Peningkatan Pemahaman Siswa pada Materi Bangun Ruang melalui Cooperative Learning Di SDN 1 Balongrejo - Ni'matul Ela Defita (Algebra: Journal of Matematics, Statistics and Computation, 2025)
This study was motivated by the low level of understanding and learning outcomes of fifth-grade students in the topic of solid geometry, as indicated by low average scores, low learning mastery, and limited student participation in mathematics learning. The study aimed to improve students’ understanding through the implementation of the Cooperative Learning model supported by realia media in learning solid geometry. This research employed Classroom Action Research conducted in two cycles. The subjects of the study were 12 fifth-grade students of SDN 1 Balongrejo, while the object of the study was students’ understanding and learning outcomes in solid geometry. Data were collected through tests, observation, questionnaires, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The results showed that the implementation of the Cooperative Learning model with realia media improved students’ learning outcomes, as reflected in the increase in the average score from 57.5 in the pre-cycle to 74 in Cycle I and 83 in Cycle II. The percentage of learning mastery also increased from 33.33% to 75.00% and 83.33%. The implication of this study is that cooperative learning supported by realia media can serve as an alternative mathematics teaching strategy that is more concrete, active, and meaningful for elementary school students.